(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Rivastigmine and donepezil are both increase attention and working memory functioning. Objective: The purpose of the present study was to observe and compare the efficacy and safety of rivastigmine and donepezil in mild to moderate dementia. Methodology: This observational study was conducted on patients with mild to moderate dementia attended in the Out-patient Departments of Neurology, Medicine and Psychiatry, Sylhet MAG Osmani Medical College Hospital, Bangladesh during the period from July 2017 to June 2018. Patients with mild to moderate dementia were selected of which group A was treated with rivastigmineand group B was treated with donepezil by respective physician and Mini-Mental State Examination (MMSE) was recorded in all participants before initiation of treatment and at 4th week and at 12th week of treatment. Result: A total of 230 patients with mild to moderate dementia were selected of which 115 were treated with rivastigmine (Group-A) and another 115 were treated with donepezil (Group-B). In course of follow up period 11 patients from group A and 13 patients from group B were dropped out. Finally 104 patients of group-A and 102 patients of group-B were accounted as study subjects for statistical analysis. Out of 230 patients the mean age was 64.89 ± 6.82 years and 63.67 ± 7.02 in group-A and group-B respectively (p=0.204). Vascular dementia was 60(57.7%) patients and Probable Alzheimer Disease was in 44 (42.3%) patients in Rivastigmine treated group. It was 47 (46.1%) and 55 (53.9%) respectively in Donepezil treated group (p=0.095).The mean duration of dementia was 18.53 ± 9.25 months in group-A and 20.82 ± 11.38 months in group-B (p=0.114).The changes of mean MMSE score from 14.39 ± 2.95 at baseline to 16.37 ± 3.21 at 4th week and to 16.37 ± 3.21 at 12th week in Rivastigmine treated group (p<0.001). It was 15.05 ± 3.49, 15.84 ± 3.86 and 19.19 ± 4.38 respectively in Donepezil treated group at the 12th week (p<0.001). The percentage increment of MMSE score from baseline was 14.29% at 4th week and 41.43% at 12th week of treatment in rivastigmine treated group (p<0.001). It was 6.29% and 30.86% in donepezil treated group (p<0.001). When percentage increment of MMSE score were compared between two treatment group, there were significantly higher percentage increment of MMSE score in rivastigmine treated group compared to donepezil treated group estimated at 4th week (p<0.001) and at 12th week of treatment (p=0.001). Conclusion: Treatment with rivastigmine and donepezil increases cognitive function by measurement of MMSE in patients with mild to moderate dementia. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 8-12